Upaya Kantor Urusan Agama dalam Meminimalisir Pernikahan Dibawah Umur - Muhammad Syifa’uddin; R. Zainul musthofa (HOKI : Journal of Islamic Family Law, 2025)
Although the minimum age for marriage has been set by law, underage marriage is still a major social problem in many parts of Indonesia. The purpose of the study describes how efforts and tactical initiatives undertaken by the Office of Religious Affairs (KUA) to stop and reduce child marriage. The methods used in this research are in-depth interviews, field observations to collect qualitative data. From the research conducted, it shows that the KUA has implemented education to reduce, and suppress the number of early marriages. Among other preventive measures, according to the research findings is the conduct of official meetings attended by village heads who are then expected to provide education to their communities.